1978
DOI: 10.1002/ajh.2830040102
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide generation by human monocytes and macrophages

Abstract: Intracellular and extracellular superoxide (O2.-) generation by human monocytes and macrophages was quantitated by the nitroblue tetrazolium (NBT) reduction method. Human monocytes reduced 4.4 +/- 0.9 nmoles/10(6) cells/15 minutes with an increase to 12.4 +/- 1.3 during phagocytosis of zymosan. Based on inhibition by superoxide dismutase, superoxide generation of these cells was 1.8 +/- 0.9 nmoles in the resting state and 16.8 +/- 2.8 nmoles with zymosan phagocytosis. Human macrophages obtained by thoracentesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…As reported by others (22,(29)(30)(31), SOD or SOD adsorbed to latex particles (but not inactivated SOD) partially inhibited NBT reduction in a concentration-dependent fashion (data not shown). These data indicate the role of superoxide anion (02-) in NBT reduction by intact phagocytes.…”
Section: Contribution Of Different Types Of Leukocytes To Reduction Osupporting
confidence: 61%
See 1 more Smart Citation
“…As reported by others (22,(29)(30)(31), SOD or SOD adsorbed to latex particles (but not inactivated SOD) partially inhibited NBT reduction in a concentration-dependent fashion (data not shown). These data indicate the role of superoxide anion (02-) in NBT reduction by intact phagocytes.…”
Section: Contribution Of Different Types Of Leukocytes To Reduction Osupporting
confidence: 61%
“…Thereafter, reaction mixtures were processed and assayed as described by Baehner and Nathan (20), except that the reduced dye was extracted in 3 ml of pyridine. The amount of NBT reduced was calculated with the extinction coefficient E = 2.8 mM -I cm -I (22). lntracellular Location of Reduced NBT.…”
mentioning
confidence: 99%
“…We have shown that through this mechanism, the cells inhibit OH' production, and also myeloperoxidase-dependent production of HOCL. Since these are the most likely contenders for oxidant-mediated tissue damage by neutrophils and other phagocytes (4,28), our results show how red cells could buffer the environment against harmful effects of these cells.…”
Section: Discussionmentioning
confidence: 93%
“…Human macrophages appear capable of generating substantial amounts of superoxide anion (O 2 * − ) during phagocytosis which may play an important role in bactericidal and other cell functions [44], so macrophages play an essential role not only in the defense against the infection, but are involved in many various pathological processes [45].…”
Section: Ifn-gamma Is Secreted By Thymus-derived (T) Cells Under Certmentioning
confidence: 99%